Effect of CuO doping on the performance of LaB6 interlayer films in Al/CuO:LaB6/p-Si/Al diodes - Ocaya, Richard O.; Al-Sehemi, Abdullah G.; Tataroglu, Adem; Dere, Aysegul; Erol, Ibrahim; Aksu, Mecit; Yakuphanoğlu, Fahrettin (Elsevier, 2023)
This study investigates the fabrication and performance analysis of Al/CuO:LaB6/p-Si/Al diodes with CuO-doped LaB6 interlayer films of varying concentrations (1%, 5%, and 10%). Experimental evidence demonstrates the limitations of 0% CuO doping, as pure LaB6 lacks a significant barrier height, resulting in ohmic behavior unsuitable for intended applications. Through comprehensive analyses under varying illuminations (20-100 mW/cm2) and frequencies (10 kHz-1 MHz), the study reveals that controlling CuO doping in LaB6 significantly enhances the effective barrier height at the LaB6:CuO heterojunction, improving rectification properties. This enhancement enables the diode to be well-suited for high-speed photonic devices utilizing one-step photoemission. The findings contribute to the development of high-performance LaB6-based devices, advancing photonic technologies by emphasizing the advantages of CuO doping.
Keywords: One-step photoemission; Copper oxide (CuO); Lanthanum hexaboride (LaB6); Photonic device; Transient response; Frequency effect